The Effectiveness of Productive Waqf in Supporting Sustainable Development: An Analysis of its Impact on Socio-Economic Growth - Eka Putriana; Diva Aulia (Penerbit Hellow Pustaka, 2026)
Productive waqf is increasingly viewed as a strategic instrument in supporting the achievement of sustainable development goals (SDGs) through the provision of long-term, sustainable social funding. This study aims to analyze the effectiveness of productive waqf in supporting sustainable development and its impact on community socio-economic growth. Using a literature review method, this study examines various academic sources discussing the concept, regulation, implementation, and impact of productive waqf. The study results indicate that productive waqf has the potential to support socio-economic development through increased income, job creation, poverty alleviation, empowerment of MSMEs, and the provision of social services such as education and health. However, this effectiveness is still affected by various obstacles such as weak governance, lack of professionalization of nazhir (managers), and suboptimal investment management. This study emphasizes the need to strengthen institutional capacity, transparency, and integrate waqf into national development strategies so that its benefits can be felt sustainably. These findings contribute to the development of Islamic social finance theory and practice and serve as a reference for policymakers in optimizing the role of productive waqf for community welfare.